Dataset associated with "A nonmonotonic precipitation response to changes in soil moisture in the presence of vegetation" - Drager, Aryeh Jacob; Grant, Leah D.; van den Heever, Susan C. (Colorado State University. Libraries, 2022)
In many parts of the world, humans rely on afternoon rainfall for their water supply. However, it is not fully understood how land surface properties influence afternoon precipitation. In fact, disagreement remains regarding the relative prevalence of “wet-soil advantage” regimes, in which wet soils receive more precipitation than do dry soils, and “dry-soil advantage” regimes, in which the opposite occurs. Recent studies have proposed that the permanent wilting point (PWP) soil moisture threshold influences the location and organization of convective clouds. Motivated by this work, we investigate how changes in soil moisture relative to the PWP affect the timing and amount of surface rainfall, as well as how this response depends on the presence or absence of vegetation. This investigation is carried out by conducting several series of high-resolution, idealized numerical experiments using a fully coupled, interactive soil-vegetation-atmosphere modeling system. From these experiments, a new soil moisture-precipitation relationship emerges: in the presence of vegetation, simulations with moderately dry soils, whose initial liquid water content slightly exceeds the PWP, generate significantly less surface precipitation than do those with the driest or wettest soils. This result suggests that simulated “wet-soil advantage” and “dry-soil advantage” regimes may not necessarily be mutually exclusive, insofar as extremely wet and extremely dry soils can both exhibit an “advantage” over moderately dry soils. This non-monotonic soil moisture-precipitation relationship is found to result from the PWP’s modulation of transpiration of water vapor by plants. In the absence of vegetation, a wet-soil advantage occurs instead in these idealized simulations.
This dataset contains the data and scripts necessary to reproduce the results of the associated publication. Model output files are not included, but some processed results are provided. The model itself and the scripts used to run the model are included in the dataset. All scripts for processing the raw model outputs and creating figures are included.
Department of Atmospheric Science
Walter Scott, Jr. College of Engineering
Keywords: soil moisture; precipitation; rainfall; atmospheric convection; tropical convection; shallow convection; convective processes; cloud processes; land-atmosphere interactions; vegetation; evapotranspiration; permanent wilting point; stomatal conductance; stomatal resistance; cloud-resolving model; numerical modeling; boundary-layer processes; soil texture; idealized modeling; RAMS model